Enhanced TH17 Responses in Patients with IL10 Receptor Deficiency and Infantile-onset IBD. Issue 11 (November 2017) - Shouval, Dror S.; Konnikova, Liza; Griffith, Alexandra E.; Wall, Sarah M.; Biswas, Amlan; Werner, Lael; Nunberg, Moran; Kammermeier, Jochen; Goettel, Jeremy A.; Anand, Rajsavi; Chen, Hannah; Weiss, Batia; et al.
Abstract : Background: IL10 receptor (IL10R) deficiency causes severe infantile-onset inflammatory bowel disease. Intact IL10R-dependent signals have been shown to be important for innate and adaptive immune cell functions in mice. We have previously reported a key role of IL10 in the generation and function of human anti-inflammatory macrophages. Independent of innate immune cell defects, the aim of the current study was to determine the role of IL10R signaling in regulating human CD4 + T-cell function. Methods: Peripheral blood mononuclear cells and intestinal biopsies cells were collected from IL10/IL10R-deficient patients and controls. Frequencies of CD4 + T-cell subsets, naive T-cell proliferation, regulatory T cell (Treg)-mediated suppression, and Treg and TH 17 generation were determined by flow cytometry. Transcriptional profiling was performed by NanoString and quantitative real-time polymerase chain reaction. RNA in situ hybridization was used to determine the quantities of various transcripts in intestinal mucosa. Results: Analysis of 16 IL10- and IL10R-deficient patients demonstrated similar frequencies of peripheral blood and intestinal Tregs, compared with control subjects. In addition, in vitro Treg suppression of CD4 + T-cell proliferation and generation of Treg were not dependent on IL10R signaling. However, IL10R-deficient T naive cells exhibited higher proliferative capacity, a strong TH 17 signature, and an increase in polarization toward TH 17 cells, compared with controls. Moreover, the frequency of TH 17 cells was increased in the colon and ileum of IL10R-deficient patients. Finally, we show that stimulation of IL10R-deficient Tregs in the presence of IL1β leads to enhanced production of IL17A. Conclusions: IL10R signaling regulates TH 17 polarization and T-cell proliferation in humans but is not required for the generation and in vitro suppression of Tregs. Therapies targeting the TH 17 axis might be beneficial for IL10- and IL10R-deficient patients as a bridge to allogeneic hematopoietic stem cell transplantation. Abstract : Article first published online 11 October 2017.Supplemental Digital Content is Available in the Text.